Mineral supplementation in weaner lambs - Selaive-Villarroel, Arturo Bernardo; Cattani, José Carlos; Figueiró, Paulo Roberto Pires; Oliveira, Nelson Manzoni de; Silva, João Gilberto Corrêa da (Pesquisa Agropecuaria Brasileira, 1991)
The effects of two different mineral supplements, a commercial mineral mixture (7.83% P and 9.50% Ca) and sodium chloride (35.0% Na and 25.0% Cl) were evaluated in respect to liveweight and wool production on lambs from weaning to early age. The trial was carried out at EMBRAPA-CNPO, the Sheep National Research Center of Brazil, located in Bagé, RS, during February/84 to March/85. A total of 90 Corriedale lambs, initially ageing 4-5 months, were used. Lambs were run on native pasture at a stocking rate of 10 lambs/ha, receiving hay supplementation during winter. Data on liveweight development, greasy wool production, mineral intake and pasture mineral content were collected. The average daily mineral intakes were 2.08 g (ranging from 0.56 to 3.55 g) for the commercial mixture and 4.50 g (ranging from 2.30 to 7.41 g) for sodium chloride. The native pasture samples showed levels of 0.12% of P and 0.16% of Ca. Comparing to the control group (no supplementation), the effects did not significantly increase either the liveweight or wool production in both treatments. The intake of the commercial mineral mixture was lower than that expected, as well as below the animal requirement.